МУСОБАҚА ФОАЛИЯТИ ДАВРИДА ЮҚОРИ МАЛАКАЛИ СПОРТЧИЛАР НАТИЖАЛАРИНИНГ ЎСИШ САМАРАДОРЛИГИ ТАҲЛИЛИ - Калжанов, П.; Калжанов, Р. (SCIENCE and SOCIETY, 2025)
The article analyzes the results of volleyball players of the Republic of Karakalpakstan over the past 10 years and makes statistical conclusions about the advantages and disadvantages of athletes as a result.
Keywords: volleyball players; competitions; gold medals; international competitions; team boats; trend